Molecular epidemiology and genetic dynamics of carbapenem-resistant hypervirulent Klebsiella pneumoniae in China - Li, Xiangchen; Chen, Sisi; Lu, Yewei; Shen, Weifeng; Wang, Weixin; Gao, Junli; Gao, Junshun; Shao, Pingyang; Zhou, Zhuxian (Frontiers in Cellular and Infection Microbiology, 2025)
Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CRhvKP) poses a significant global health threat due to its enhanced virulence and resistance. This study analyzed 5,036 publicly available K. pneumoniae genomes from China (2005–2023), identifying 1,538 CRhvKP genomes, accounting for 44.6% of carbapenem-resistant isolates and 69.5% of hypervirulent isolates. Predominant carbapenemases included blaKPC (92.1%), with an increasing prevalence of blaNDM and blaOXA-48-like genes. Most isolates (93.6%) carried both aerobactin and yersiniabactin genes. The genetic background showed high diversity, characterized by 36 sequence types (STs) and 22 capsule types, with high-risk endemic STs such as ST11, ST15, and ST23 being predominant. ST23 demonstrated enhanced virulence, whereas ST11 carried more resistance genes but showed minimal presence of iroBCDN genes. A core genome MLST analysis revealed that 89.0% of CRhvKP isolates clustered into 131 clonal groups, indicating widespread dissemination, particularly in eastern China. CR and hv plasmids, primarily IncF, IncH, and IncR types, showed distinct community structures, with CR plasmids demonstrating higher mobility and diversity. Crucially, we identified 40 CR-hv convergent plasmids across five STs, likely resulting from plasmid fusions, which have become increasingly prevalent in eastern China over the last decade. Furthermore, chromosomal integration of hv genes and blaKPC-2 was detected, underscoring the stable inheritance of these traits. Class 1 Integrons were present in 84.5% of CRhvKP strains, most notably in ST11 and least in ST23. These integrons harbored genes that confer resistance to various antibiotics, including blaIMP and blaVIM, with their content varying across different STs. This study highlights the genetic complexity, rapid dissemination, and increasing prevalence of CRhvKP in China, emphasizing the urgent need for enhanced genomic surveillance and targeted interventions to mitigate the threat posed by these multidrug-resistant and hypervirulent strains.